Preparing Teachers for the 21st Century Using PBL as an Integrating Strategy in Science and Technology Education - Brears, Lindsay; MacIntyre, Bill; O’Sullivan, Gary (Design and Technology Education: An International Journal, 2011)
This paper explores the foundational principles of ProblemBased Learning (PBL) as an integrative teaching strategy designed deliberately to cross discipline boundaries in order to make meaningful and lasting connections. The authors suggest that while PBL has in recent times has largely manifested towards a method of inquiry within a single discipline the founding principles and key characteristics that inform PBL may be applied to solving technological inquiry where an understanding and application of scientificprinciples is fundamental in informing and developing the preferred solution. This paper highlights that in order to be effective classroom educators, in an ever increasing and complex world, pre-service teachers’ need to develop robust mental models and metacognitive skills that are transferable. In supporting this development the rationale and the application of PBL as an integrated teaching and learning strategy in pre-service science and technology education will be examined. This paper suggests that PBL is an effective strategy in supporting inquiry of an interdisciplinary nature as well as developing dispositions that embrace collaborative inquiry and reflective practice.